Feeding Behavior and Nutritional Status of Toddlers in Rural Areas - Septyani, Ima Aulia; Faridah, Umi; Jauhar, Muhamad (Indonesian Journal of Health Research and Development, 2025)
Nutritional status is a serious public health problem because it is associated with an increased risk of mortality and morbidity. This problem is caused by caregivers' feeding habits, which can affect the nutritional status of toddlers. The impacts that arise if not handled properly will pose a risk of stunted growth and development of toddlers. This research analyses the relationship between feeding behaviour and nutritional status in toddlers. The research design uses correlation analysis with a cross-sectional approach. The independent variable is feeding behaviour, and the dependent variable is the nutritional status of toddlers. This research was conducted in December 2024 in the Dawe Kudus Community Health Center Work Area. A total sample of 71 caregivers was selected using random sampling techniques. The research instruments used the Child Feeding Questionnaire, digital scales, and microtois. Data analysis used the Spearman Rank (rho) test. The research results showed a statistically significant relationship between feeding behaviour and the nutritional status of toddlers, with a value of p = 0.003 (p < 0.05). This feeding behaviour contributes to improving the nutritional status of toddlers, so there is a need for further intervention to improve caregiver behaviour in feeding so that the nutritional status of toddlers is optimal.